TRANSFER OF TECHNOLOGY IN UKRAINE: CURRENT CHALLENGES - Olexander P. Svitlychnyy (Alfred Nobel University Journal of Law)
The article is devoted to the study of the problematic issue of technology transfer in today's conditions. Legislators and by-laws regulating relations in the field of technology transfer are analyzed. Attention is drawn to the importance of scientific technologies and their implementation in the activities of industrial enterprises, which is an indispensable development of the economic growth of many leading economically developed countries, as well as a determining factor in the progress of society and the improvement of the welfare of citizens. Informational, analytical and statistical data on the impact of technology transfer on the financial condition of enterprises, institutions and organizations in relation to budget funds are presented. Among the positive financial indicators, based on the analysis of statistical data and scientific literature, attention is drawn and problems hindering the integration of the technology transfer process in domestic industrial enterprises are identified. In particular, these are: migration of scientists; insufficient amounts of funding for innovative activities; low innovative activity of active enterprises, which leads to a reduction in the share of innovative products both in the structure of production and in exports; low level of state support for innovation and demand for high-tech products; lack of stimulating technology transfer mechanisms. Using the example of the report of the State Enterprise «Ukrainian Institute of Intellectual Property» for 2021, attention is drawn to the decline in innovative activity of domestic enterprises. It is emphasized that in the conditions of a full-scale war between Russia and Ukraine, state support for innovations, inventors, and other authors of intellectual property rights is a guarantee of increasing the economic potential and military-industrial complex of the state. Addresses existing problematic issues of state security regarding the transfer of technology, protection of secret inventions, commercial secrets, other objects of intellectual property law, and suggests ways of solving problematic issues in the field of technology transfer in Ukraine.